Writers, Manuscripts, Collectors: Modern Authorship and the Fin-de-Siècle Origins of the Literary Archive - Tim Sommer (Authorship, 2023)
During the late nineteenth and early twentieth century, collecting authors’ material remains developed from a private pursuit into a public mission, a history that is coupled to the emergence of modern institutions such as the research library and the literary archive. Authors of the period were themselves both aware of and involved in the market for literary manuscripts and the increasingly institutionalized culture of collecting writers’ papers. This article looks at literary fiction as a contemporary medium in which this moment of transition was mirrored. As a case study, I focus on the early writings of Edith Wharton – retracing a gradual shift in her creative interests from the autographs of contemporary or near-contemporary writers to those of canonized figures and from collecting as an amateur occupation to collecting as a professional endeavour.